The Effect of the Control System and Promotion on the Performance of Makassar City DPRD Office Employees - Sani, Amar; Solihin Matalatta, Rahmi, (Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine the effect of the control and promotion system on the Makassar city DPRD office, where the study used a saturated sample with a sample of 30 respondents. The analysis method used is Multiple Linear Regression, with T test and F test with data processing tools using the SPSS For Windows Version 22 program. knowing the influence of the control system and promotion in the Makassar city DPRD office, where the study used a saturated sample with a sample of 30 respondents. The analysis method used is Multiple Linear Regression, with T test and F test with data processing tools using the SPSS For Windows Version 22 program Kata Kunci: Control System, Promotion and Employee Performance